2019
DOI: 10.1101/515528
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Planar differential growth rates determine the position of folds in complex epithelia

Abstract: Folding is a fundamental process shaping epithelial sheets into 3D architectures of organs. Initial positioning of folds is the foundation for the emergence of correct tissue morphology. Mechanisms forming individual folds have been studied, yet the precise positioning of the folds in complex, multifolded epithelia is an open question. We present a model of morphogenesis, encompassing local differential growth, and tissue mechanics to investigate tissue fold positioning. We use Drosophila melanogaster wing ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 54 publications
(50 reference statements)
0
11
0
Order By: Relevance
“…Further experiments are needed to define the mechanical interaction between the BM and columnar cells and to understand how feedback between the cells and the BM leads to coordinated growth. Several recent simulation studies have identified an important role for the BM and ECM in guiding fold formation in the growing wing disk (see Figure ), and in the overall mechanical properties of the wing disk (Atzeni, Lanfranconi, & Aegerter, ; Keller, Lanfranconi, & Aegerter, ; Tozluoğlu et al, ). How the basement membrane and ECM are temporally regulated to tune stress in the wing disk may have a profound effect on wing disk growth (Pastor‐Pareja & Xu, ).…”
Section: The Role Of Mechanical Forces In Wing Disk Morphogenesismentioning
confidence: 99%
“…Further experiments are needed to define the mechanical interaction between the BM and columnar cells and to understand how feedback between the cells and the BM leads to coordinated growth. Several recent simulation studies have identified an important role for the BM and ECM in guiding fold formation in the growing wing disk (see Figure ), and in the overall mechanical properties of the wing disk (Atzeni, Lanfranconi, & Aegerter, ; Keller, Lanfranconi, & Aegerter, ; Tozluoğlu et al, ). How the basement membrane and ECM are temporally regulated to tune stress in the wing disk may have a profound effect on wing disk growth (Pastor‐Pareja & Xu, ).…”
Section: The Role Of Mechanical Forces In Wing Disk Morphogenesismentioning
confidence: 99%
“…Therefore, passive tension built up in the ECM (perhaps that is generated over time due to differential growth patterns) does not contribute significantly to shape generation, at least for the bent profile of the disc cross-section along the AP axis. Hence, our study suggest another possible mechanism which is different than differential growth hypothesis 39 to drive fold formation along the orthogonal dorsal-ventral axis. Perturbation studies that chemically dissolve collagen revealed that the ECM is essential to maintain the shape of the wing disc.…”
Section: Discussionmentioning
confidence: 61%
“…ECM remodeling follows the growth and division of epithelial cells in the wing disc 12 . A high growth rate of epithelial cells in comparison with ECM remodeling, can lead to accumulation of tensile stress in the ECM 39 . In other contexts, cell stresses are converted into pre-strains within the ECM 40 .…”
Section: Passive Tension Within the Ecm Is Not Sufficient To Bend Thementioning
confidence: 99%
See 2 more Smart Citations